John Henry Newman come apologeta secondo P. Stanley L. Jaki, O.S.B - Barrajón Muñoz, Amador Pedro (Alpha omega, 2011)
The article presents the way in which the Blessed John Henry Newman did Apologetics according to the Hungarian Benedictine scientist and philosopher Stanley Jaki. Jaki wrote towards the end of his life several books on the great English convert. He sees Newmans’s way of doing Apologetics as valid also in our days. The great themes of Apologetics such as the conscience of sin, the desire of redemption, in which the existence of a personal God can been foreseen, are at the very center of Newman’s works. For him it was important to recognize the capacity of the human intellect to go beyond the mere sensitive data and to make judgments on religious matters (illative sense). Jaki considers that the deep vision and the iron logic of Newman’s argumentations are also valid for the construction of the contemporary “new Apologetics”.